A Study on Online Learning Environment - Yaser Qureshi (AG Volumes, 2022)
Traditional face-to-face classrooms have been transformed into online and hybrid learning spaces as a result of technological advancements. Students' favourable attitudes about such sessions and their own personal experiences and expectations are important components of hybrid learning setups that might contribute to its success and overall happiness among students. As students get more experience in utilising an OLE for learning, the most significant things that become crucial are not technical concerns and computer literacy but rather the attitudes of students and instructors as well as the drive to develop and learn.In the field of educational technology, an online learning environment, abbreviated as OLE, is a web-based platform for the digital parts of courses of study, which are often housed inside educational institutions. They have materials, activities, and interactions that fit into the structure of a course, and they can be graded in many different ways.